2020
DOI: 10.5617/nordina.7396
|View full text |Cite
|
Sign up to set email alerts
|

Oi! Sjå på den! – Funn av naturelement som utgangspunkt for utforskande naturfaglege samtalar mellom barn (5-6 år) og pedagogar

Abstract: The study examines what characterizes situations that facilitate young children´s participation in exploratory scientific dialogues in outdoor education. By using action cameras mounted to the chest of three children (5-6 years) and two pedagogues during an outdoor session, recordings of 106 scientific dialogues are identified and analyzed in terms of categories describing the communicative project (the purpose) of the dialogues. These categories are: exploring, informing/presenting, and calling for attention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…This supports the assumptions made earlier based on Chouinard et al (2007) and Thulin's (2010) findings, that contexts where children are presented to both living and non-living objects originating from nature might enhance question-asking in the children. These findings are also in line with Skalstad (2020) and Waters and Maynard (2010), who found that nature elements seem to trigger engagement and interest in the children.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This supports the assumptions made earlier based on Chouinard et al (2007) and Thulin's (2010) findings, that contexts where children are presented to both living and non-living objects originating from nature might enhance question-asking in the children. These findings are also in line with Skalstad (2020) and Waters and Maynard (2010), who found that nature elements seem to trigger engagement and interest in the children.…”
Section: Discussionsupporting
confidence: 90%
“…According to Thulin (2006), this may leave the child to seek his/her own explanations. However, other studies have shown that having an open dialogue with the children may provide the children with good learning opportunities and deeper understanding and knowledge of nature (Gustavsson & Pramling, 2014;Skalstad, 2020). It is therefore evident that to take full advantage of the learning opportunities in situations where children ask questions, it is important to have knowledge about children's questioning as well as the teacher's responses to these.…”
Section: Responding To Children's Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These natural environmental resources may include life science and nature (e.g., leaves, rotting logs, insects, animals and sea life, plants, and trees) and Earth science (e.g., rocks and gems, bubbles, water, and the ocean) [74]. Studies of preschool-and school-children exploring in a natural outdoor environment show that children's findings of natural elements and objects (e.g., insects, plants, rocks, or puddles) seem to interest and engage the children [75,76]. The natural outdoor environment is here defined as an area outside the kindergarten or school's area that is largely unaffected by human intervention, like, for example, a forest, river, or seashore area.…”
Section: Future Directionsmentioning
confidence: 99%
“…Å beskrive sensoriske opplevelser krever språk og trening, og utforskende samtaler om smaksopplevelser kan stimulere barn til å smake på nye smaker . Når barnehagelaerer tar del i barnets sanselige opplevelser kan spontane spørsmål og ytringer under og etter slik utforsking utvikle seg til faglige samtaler mellom barnet og laerer (Skalstad, 2020). Barnas samtaler i eksempel 24 ble også gjentagende og akkumulert over tid ettersom barna resten av dagen fortsatte å utforske og snakke om smakskombinasjoner.…”
Section: Barna Snakket Om Sine Sanselige Og Praktiske Erfaringer Med ...unclassified